Pengembangan Media PANDIGI Melalui Model Berdiferensiasi pada Materi Puisi Rakyat - Kusumo, Rino; Lutfi Syauki Faznur; Chandra Gumilar (Jurnal Bintang Pendidikan Indonesia, 2025)
This research is based on the lack of understanding in learning Indonesian in folk poetry materials, the difference between students’ learning styles and unsupportive learning media is an obstacle for students in the learning process in the classroom so that students get bored easily. The purpose of this study is to describe the stages of PANDIGI learning media development with a differentiated model on folk poetry materials and to find out the validity and practicality of the development of the developed learning media. The type of research used is research and development using the ADDIE model, (analyze, design, development, implementation, evaluation). This research was conducted at SMPN 18 South Tangerang with the research subjects of grade VII.8 students totaling 41 students. The results of the study show that this learning media is valid and practical to use. The results of the assessment score of material experts were 85.71, and media experts were 86.6 which showed decent information without revision, as well as research from students conducted using a questionnaire showed a score of 84.36 which means very good, so it can be concluded that the PANDIGI website gets a very good and very decent category.